Evaluation of Bentonite Mixed Indigenous Clays for Development of Clay Liners - Muhammad Israil; Muhammad Ashraf; Muhammad Fahim; Rashid Rehan; Sajjad Wali Khan; Shabir Hussain (Civil Engineering Journal, 2020)
This study presents experimental investigation of indigenous clays mixed with Bentonite to assess their suitability in potential use as clay liners. Soil samples with 0, 4, 8, and 12% Bentonite content from three different sites in Peshawar region were tested for various geotechnical properties. Grain size distribution, specific gravity, Atterberg limits and free swell were found through laboratory tests using appropriate ASTM procedures. Maximum dry density and optimum moisture content were calculated using Atterberg limits in available relationships. Finally, one dimensional consolidation tests were conducted to find relevant parameters for calculating hydraulic conductivity. A decrease in specific gravity, increase in free swell, and in optimum moisture content, decline in maximum dry density and hydraulic conductivity was observed with increase in Bentonite content across all three soil samples. During free swell, the soil clusters become larger leading to formation of floccules resulting in the narrowing of inter-particle space and thus blocking of permeable paths. It is concluded that 8% Bentonite content by weight yields a suitable mixture for a clay liner that has hydraulic conductivity in the range of recommended limits.